BRCA1 and BRCA2 Mutations Other Than the Founder Alleles Among Ashkenazi Jewish in the Population of Argentina - Solano, Angela R.; Liria, Natalia C.; Jalil, Fernanda S.; Faggionato, Daniela M.; Mele, Pablo G.; Mampel, Alejandra; Cardoso, Florencia C.; Podesta, Ernesto J. (Frontiers in Oncology, 2018)
In Ashkenazi Jewish (AJ) high risk families 3 mutations [2 in BRCA1 (c. 68_69del and c.5266dup) and 1 in BRCA2 (c.5946del)] account for the majority of high risk breast and ovarian cancer cases in that ethnic group. Few studies with limited number of genotyped individuals have expanded the spectrum of mutations in both BRCA genes beyond the 3 mutation panel. In this study, 279 high risk individual AJ were counseled at CEMIC (Centro de Educación Médica e Investigaciones Clínicas), and were genotyped first for the 3 recurrent mutation panel followed by Next Generation Sequencing (NGS) of BRCA1 BRCA2 in 76 individuals who tested negative for the first genotyping step. Of 279 probands (259 women), 55 (50 women) harbored one of the 3 mutations (19.7%); Of 76 fully sequenced cases (73 women), 6 (5 women) (7.9%) carried a pathogenic mutation: in BRCA1, c.2728C>T - p.(Gln910*); c.5407-?_(*1_?)del and c.5445G>A - p.(Trp1815*); in BRCA2, c.5351dup - p.(Asn1784Lysfs*3); c.7308del - p.(Asn2436Lysfs*33) and c.9026_9030del - p.(Tyr3009Serfs*7). Of 61 mutation carriers the distribution was as follows: 11 cancer free at the time of genotyping, 34 female breast cancer cases with age range 28–72 years (41.6 ± 9.3), 3 male breast cancer cases with age range 59–75 years (65 ± 7.3), 6 breast and ovarian cancer cases with age range 35–60 years (breast 40.4 ± 5.2; ovary 47.8 ± 7.2) and 7 ovarian cancer cases with age range 41–77 years (60.6 ± 13.3). This information proved highly useful for counseling, treatment, and prevention for the patient and the family. In conclusion comprehensive BRCA1/2 testing in AJ high risk breast ovarian cancer cases adds valuable clinically relevant information in a subset of cases estimated up to 7% and is therefore recommended.